2014
DOI: 10.21836/pem20140410
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology, clinical presentation and current treatment options of equine malignant melanoma – a review of the literature

Abstract: Summary: This review aims at giving an overview of the aetiology, genetic basis and clinical signs of equine malignant melanoma (EMM), the diagnostic work-up and the current treatment options. The established association between certain genetic features and melanoma formation in horses is reviewed. Typically, grey horses are affected with EMM. Typical predilection sites are the ventral tail, perianal region, eyelids, lips, parotid, or guttural pouches. Tumours usually grow slowly, but frequently metastasize ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…In contrast, equine melanocytic tumors have a very distinct clinical course. They usually emerge on cutaneous and mucocutaneous localizations such as the perianal region, tail, lips, eyelids, genital area, and parotid region, with a higher prevalence in gray horses due to genetic predisposition [ 9 , 10 , 11 , 12 , 13 ]. Even when possessing histological features of malignancy, these tumors tend to present a prolonged benign behavior, distinguished by slow mass expansion, with invasion and metastasis being rarely reported [ 3 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, equine melanocytic tumors have a very distinct clinical course. They usually emerge on cutaneous and mucocutaneous localizations such as the perianal region, tail, lips, eyelids, genital area, and parotid region, with a higher prevalence in gray horses due to genetic predisposition [ 9 , 10 , 11 , 12 , 13 ]. Even when possessing histological features of malignancy, these tumors tend to present a prolonged benign behavior, distinguished by slow mass expansion, with invasion and metastasis being rarely reported [ 3 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curik et al (2013) described three pathologically defined clinical patterns: (i) the majority of cases present as slowly growing melanomas over many years without evidence of regional or distant metastases; (ii) malignant transformation of a benign melanoma (melanocytoma); and (iii) the rare cases of melanomas that are malignant from onset. A recent review by Moore et al (2013) described melanomas as a variably pigmented neoplasia with the capacity of local invasion and metastasis, and Cavalleri et al (2014) reported that this condition may present itself in a more advanced stage as a multicentric malignancy (equine malignant melanoma).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their initially slow invasive growth, they frequently metastasize later (Baker and Leyland 1975, Valentine 1995, Fleury et al 2000a, Smith et al 2002. For further information on clinical signs and conventional therapeutic options, the reader is referred to recent extensive reviews on the matter (Metcalfe et al 2013, Moore et al 2013, Phillips and Lembkke 2013, Cavalleri et al 2014). …”
Section: Introductionmentioning
confidence: 99%